PREJUDICE TOWARDS AFRICAN-AMERICAN CHARACTERS IN MILDRED D. TAYLOR’S THE ROAD TO MEMPHIS NOVEL - Galih Anom Ismaul Ramadhan; Indah Sari Lubis; Aries Utomo (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2021)
Prejudice has been a long-standing issue in our society. Although it is not essentially harmful, it can lead to various forms of antipathetic conduct such as talking against people, discriminating, or attacking them with violence. This study intends to investigate the problem of prejudice towards African-American characters portrayed in The Road to Memphis novel. There are two objectives of this study, namely: (1) to identify the forms of prejudice towards African-Americans, and (2) to analyze how the African-American characters’ response to prejudice are portrayed in The Road to Memphis novel. In order to investigate the problem of prejudice, this study utilizes Gordon Allport’s acting out prejudice and traits of prejudice victimization theory. The data were in the form of narration and dialogue, while the data source was only taken from primary source which was the novel itself. The result of this study showed that African-American in The Road to Memphis novel are portrayed to experience three forms of prejudice, namely: antilocution, discrimination, and physical attack. As for African-Americans’ responses towards prejudice, it showed that extropunitive was the most dominant trait portrayed in the novel.